2013
DOI: 10.1016/j.icarus.2012.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Model for atomic oxygen visible line emissions in Comet C/1995 O1 Hale-Bopp

Abstract: We have recently developed a coupled chemistry-emission model for the green (5577Å) and red-doublet (6300, 6364 A) emissions of atomic oxygen on comet C/1996 B2 Hyakutake. In the present work we applied our model to comet C/1995 O1 Hale-Bopp, which had an order of magnitude higher H 2 O production rate than comet Hyakutake, to evaluate the photochemistry associated with the production and loss of O( 1 S) and O( 1 D) atoms and emission processes of green and red-doublet lines. We present the wavelength-dependen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 70 publications
2
37
0
Order By: Relevance
“…The errors correspond to the standard deviation of the 12 spectra. Considering the theoretical production rates of Raghuram & Bhardwaj (2013; see Table 1 of Decock et al (2015), the 1 S/ 1 D ratio corresponding to the G/R ratio), these results confirm that H 2 O is the main parent molecule that photodissociates to produce oxygen atoms when the comet is observed at a heliocentric distance of r ∼ 1 au. This agrees with previous analyses reported for other comets (Cochran 1984(Cochran , 2008Capria et al 2010;Decock et al 2013, and references therein).…”
Section: [Oi] Linessupporting
confidence: 62%
See 1 more Smart Citation
“…The errors correspond to the standard deviation of the 12 spectra. Considering the theoretical production rates of Raghuram & Bhardwaj (2013; see Table 1 of Decock et al (2015), the 1 S/ 1 D ratio corresponding to the G/R ratio), these results confirm that H 2 O is the main parent molecule that photodissociates to produce oxygen atoms when the comet is observed at a heliocentric distance of r ∼ 1 au. This agrees with previous analyses reported for other comets (Cochran 1984(Cochran , 2008Capria et al 2010;Decock et al 2013, and references therein).…”
Section: [Oi] Linessupporting
confidence: 62%
“…The velocity width as well as the flux ratios I 6300 /I 6364 and G/R = I 5577 /(I 6300 + I 6364 ) were measured. The latter permits determining the parent species of oxygen atoms by comparing our results with the theoretical production rates provided by Raghuram & Bhardwaj (2013). However, an accurate measurement of the green line requires decontaminating this line from two C 2 lines that are blended with it at 5577.331 Å and 5577.401 Å.…”
Section: [Oi] Linesmentioning
confidence: 93%
“…Since O( 1 S) and O( 1 D) are metastable states, resonance fluorescence by solar photons is not an effective excitation mechanism for populating these states. Dissociative excitation of O-bearing neutrals by photons and photoelectrons, and thermal recombination of atomic oxygen constituted ions are the sources of these metastable states in the cometary coma (Bhardwaj & Haider 2002;Raghuram & Bhardwaj 2013). Most of the comets observed around heliocentric distance of 1 au have H 2 O as the principal constituent in the cometary coma (Bockelée-Morvan et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The model calculations for comets 103P/Hartley2 and 1P/ Halley have shown that suprathermal electron impact is an important excitation process in the formation of CO(a 3 Π), which is more important than the photodissociation of CO 2 (Bhardwaj & Raghuram 2011;. The model applied to study atomic oxygen emission lines in comets has shown that the collisional quenching in the inner coma can significantly change the observed G/R ratio Raghuram & Bhardwaj 2013, 2014Decock et al 2015). The model calculations in active comets, such as (C/1996 B2) Hyakutake and (C/1995 O1) Hale-Bopp, have shown that the G/R ratio varies as a function of projected distance and depends on the collisions in the cometary comae Raghuram & Bhardwaj 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The model applied to study atomic oxygen emission lines in comets has shown that the collisional quenching in the inner coma can significantly change the observed G/R ratio Raghuram & Bhardwaj 2013, 2014Decock et al 2015). The model calculations in active comets, such as (C/1996 B2) Hyakutake and (C/1995 O1) Hale-Bopp, have shown that the G/R ratio varies as a function of projected distance and depends on the collisions in the cometary comae Raghuram & Bhardwaj 2013). Recently, we have applied our model for the analysis of high-resolution spectroscopic observations made from the ESO very large telescope (VLT) on four comets (viz., C/2002 T7 (LINEAR), 73P-C/SchwassmannWachmann 3, 8P/Tuttle, and 103P/Hartley 2).…”
Section: Introductionmentioning
confidence: 99%